Value Relevance Atas Informasi Akuntansi Sebelum dan Sesudah Adopsi IFRS pada Perusahaan di Sektor Perdagangan Jasa dan Investasi - Wenny Tjamdinata; Juniarti Juniarti Juniarti (Business Accounting Review, 2018)
ABSTACTThe research objective was to examine the increase value relevance of accounting information after International Financial Reporting Standards (IFRS) adoption in Indonesia. Value relevance measured by the fluctuation of stock price as the investors respond of accounting information. The research conducted on Trade Service and Investing Sector in Indonesian Stock Exchange (IDX) that published their annual reports in 2007 until 2014. The observation did on 26 entities for 8 years and the number of observation were 208. This research used panel data with Stata to test and to find the best model between Pooled Least Square (PLS), Fixed Effect (FE), or Random Effect (RE). The data processing divided into 2 period, before and after IFRS adoption. Hypothesis tested was done by increasing the R2 and significant value of accounting information of EPS, BVPS, OCF per share. The research showed that IFRS adoption in Indonesian Trade Service and Investing sector increasing the value relevance.